A Cross-sectional Survey of the Determinants of Maternal Health Services Utilization among Women with Disability in Mbale District, Uganda. - Watera, Edna, Christine; Matata, James; Kyeyune, Jemimah (Student’s Journal of Health Research Africa, 2022)
Background: The study aimed to evaluate the determinants of maternal health services utilization among women with disability (WWD) in the Mbale district in Uganda. Methodology: The study approach was a mixed qualitative and quantitative cross-sectional design. The selection of study participants was by snowballing for the quantitative tool and purposively sampling for the Key Informants. A sample size of 189 women with disabilities was used in the study and 8 key informants were interviewed. Data analysis was carried out using the Statistical Package for Social Sciences (SPSS) version 22, and qualitative data were subjected to thematic analysis. Findings: The proportion of WWD utilizing MHS was found to be low in the Mbale district with only 17.7% attending four or more antenatal visits. Fear of stigma was the main barrier to the utilization of maternal health services. Health education influenced the utilization of maternal health services. Utilization of maternal health services (MHS) among women with disabilities was associated with socio-economic determinants (secondary level education, spousal support, and monthly income). Finally, there was a significant association between accessibility and the utilization of MHS. Conclusion: This study revealed that external factors form the main barriers to the utilization of maternal health services among women with disability. Recommendations: Training and equipping health facility staff to be more sensitive to and attend to the unique needs of WWD could improve the experiences of WWD seeking MHS at the health facility. This may reduce their fear of stigmatization thus improving service utilization.